Inter-regional M&As, home bias and the post-merger performance - Shuwei Sun; Tusheng Xiao; Yulong Yang; Xincheng Wang (China Journal of Accounting Studies (CJAS), 2021)
The under-performance of mergers and acquisitions (M&As) resulting from impairment of goodwill is of great interest to regulators and investors. This study investigates the performance of M&As from the perspective of home bias. The results indicate that (1) Post-merger performance is worse when purchased companies are in high-level executives' hometowns. (2) When located in the executives' hometown, listed companies pay higher premiums, and further loss of goodwill occurs in the following years. Integration efficiency after M&As is lower, as reflected in the higher degree of excess employees. (3) Cross-sectional analyses indicate that M&A under-performance only occurs when the province has a low level of market development, listed companies are non-state-owned enterprises, or listed companies' executives are older. (4) Interactive effect test results suggest that fund holding, analyst following and media coverage can alleviate the negative impact of home bias on long-term performance.
Keywords: 650; Home bias; post-merger performance; merger premium; integration efficiency